Thermodynamics - Duroudier, Jean-Paul (Industrial equipment for chemical engineering set., 2016)
Thermodynamics includes thirteen independent volumes that define how to perform the selection and calculation of equipment involved in the thirteen basic operations of process engineering, offering reliable and simple methods. Throughout these concise and easy-to-use books, the author uses his vast practical experience and precise knowledge of global research to present an in-depth study of a variety of aspects within the field of chemical engineering. The main concepts of thermodynamics are presented in detail, and their importance is demonstrated through their various practical applications. In this volume, the author provides a general introduction into the study of thermodynamics. Across the five chapters, users will find different concepts involved in the study of energy, including systems, states, energy, laws, and their associated theorems. In addition, the author provides the methods needed for understanding the machinery used in applied thermodynamics to encourage students and engineers to build the programs they need themselves.